2010
DOI: 10.1523/jneurosci.1038-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Rapidly Regulates Membrane Estrogen Receptor α Levels in Hypothalamic Neurons

Abstract: Estrogen receptors (ERs) and estrogen-binding proteins have been localized intracellularly and on the cell surface. The membraneassociated proteins initiate signaling that activates a myriad of cellular responses including the modulation of ion channels and ultimately transcription. Although many of the downstream actions of membrane ERs, including ER␣ and ER␤, have been characterized, the mechanisms regulating membrane ER levels have remained elusive in the nervous system. In the present study, we used surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 70 publications
17
116
0
Order By: Relevance
“…The possibility of surfaceexpressing receptors has also been suggested by various biochemical studies. Using surface biotinylation assays, Dominguez and Micevych (2010) demonstrated the surface expression of ERa and potential splice variants in mixed sex hypothalamic cultures, supporting evidence from reports using conjugated 17b-estradiol that ERs are expressed on the surface.…”
Section: B Surface Expression Of Erssupporting
confidence: 74%
“…The possibility of surfaceexpressing receptors has also been suggested by various biochemical studies. Using surface biotinylation assays, Dominguez and Micevych (2010) demonstrated the surface expression of ERa and potential splice variants in mixed sex hypothalamic cultures, supporting evidence from reports using conjugated 17b-estradiol that ERs are expressed on the surface.…”
Section: B Surface Expression Of Erssupporting
confidence: 74%
“…Recently, ER was reported to be present on the plasma membrane of various cell types of other systems, including the central nervous system and the blood vascular system. [18][19][20] In the case of immune cells, the intracellular calcium concentrations of T cells and macrophages increased rapidly after estradiol treatment, indicating that the presence of ER on the plasma membrane in these cells. [26][27][28] However, it has been reported that ER was not present on the plasma membrane in mouse Bcells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, expression of functional ER on the membrane was detected in various immune cells in mammals. [18][19][20] The membrane ER has been reported to have functions different from those of nuclear ER, which is traditionally known as the receptor of estrogen.…”
mentioning
confidence: 99%
“…In light of recent reports highlighting the effects of E2 on plasma membrane and ER functions in a nongenomic manner [28][29][30][31][32] and the known responsiveness of STAT5a/b proteins to E2, 23 we investigated whether exposure of endothelial cells to E2 with or without additional knockdown of STAT5a/b might affect the subcellular localization of wt BMPR2. The data in Figure 9A and 9B first confirm the effect of STAT5a/b knockdown in causing increased intracellular trapping of wt BMPR2.…”
Section: Effect Of E2 On the Subcellular Localization Of Wt Bmpr2mentioning
confidence: 99%
“…27 Moreover, STAT5 species are already recognized to mediate aspects of the sexual dimorphic phenotypes in terms of postpubertal development and gene expression. 22,23 Additionally, the known responsiveness of STAT5a/b to E2 23 and the newly recognized nongenomic effects of E2 on ER membranes itself [28][29][30][31][32] made it attractive to investigate the effects of these combinatorial modalities (STAT5a/b downregulation and E2) on trafficking of BMPR2.…”
Section: Introductionmentioning
confidence: 99%